2006
DOI: 10.1007/s00705-006-0882-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genetic diversity of hepatitis E virus (HEV) and determination of the seroprevalence of HEV in eastern China

Abstract: Hepatitis E, caused by the hepatitis E virus (HEV), is endemic in China. However, the molecular characteristics of HEV circulating in eastern China and the seroprevalence of HEV infection in eastern China are relatively unknown. In this study, 25 HEV strains, isolated from sporadic hepatitis E cases in eastern China, were sequenced in the RNA-dependent RNA polymerase region and subjected to phylogenetic analysis. These HEV strains were 74.6-98.7% identical in nucleotides and were all clustered into HEV genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 20 publications
5
41
0
Order By: Relevance
“…Multivariate analysis of the data indicated that HEV prevalence varied according to occupational activity and geographical location. Differences in HEV seroprevalence between rural and urban areas have been described (8,32), the existence of regional differences has previously been reported (26,42), and field workers in Ger- many and the United States have been identified as being at risk (9,15). In addition, it should be noted that variations in seroprevalence in different French regions did not correlate with the pig population in these regions (Table 5) but correlated with the regional variations in the frequency of car accidents due to wild boars (per 1,000 km 2 ), an indirect means to evaluate the level of contacts between humans and wild boars.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analysis of the data indicated that HEV prevalence varied according to occupational activity and geographical location. Differences in HEV seroprevalence between rural and urban areas have been described (8,32), the existence of regional differences has previously been reported (26,42), and field workers in Ger- many and the United States have been identified as being at risk (9,15). In addition, it should be noted that variations in seroprevalence in different French regions did not correlate with the pig population in these regions (Table 5) but correlated with the regional variations in the frequency of car accidents due to wild boars (per 1,000 km 2 ), an indirect means to evaluate the level of contacts between humans and wild boars.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, northern Xinjiang, without a history of hepatitis E outbreaks or epidemics, showed similar positive rates to that of eastern China (17.2%). 31 One human HEV strain, CHN-XJ-HE29, isolated from an individual of Han nationality with acute sporadic hepatitis E shared 100% nucleotide identity with swine HEV strain CHN-XJ-SW50. Furthermore, both the HEV isolates were identified from the same district in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Ltd., Singapore Science Park, Singa-pore), and negative for IgM antibodies against hepatitis A virus and hepatitis B virus core antigen and for IgG antibody against hepatitis C virus. The second group was composed of samples from 37 acute hepatitis E patients who were diagnosed by the detection of HEV RNA (7). The third group included 117 sera which were positive for anti-HEV IgM, repeatedly detected with a Genelabs kit.…”
Section: Methodsmentioning
confidence: 99%
“…There are four major genotypes of HEV identified, yet there is only a single serotype (19). In China, most sporadic cases are caused by genotype 4 (7,13).…”
mentioning
confidence: 99%